2014 First International Conference on Automation, Control, Energy and Systems (ACES) 2014
DOI: 10.1109/aces.2014.6807993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of three phase cascaded H-bridge multilevel inverter for symmetrical & asymmetrical configuration

Abstract: The previous studies have shown the drawbacks of conventional inverters, specially for high power application. From the beginning of 21st century, drastic improvement in the harmonic profile and increased power rating of MLI made them highly popular for high power application. MLI's are widely utilized in industrial field employing motor drives, static VAR compensators and renewable energy systems, etc. Basically output voltage of a MLI has multiple levels as compare to conventional inverters. This increment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The efficiency of CHBMLI is higher than conventional two‐level VSC, due to the lower switching losses [18], and it is validated experimentally by comparing Figs. 11–14 with Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of CHBMLI is higher than conventional two‐level VSC, due to the lower switching losses [18], and it is validated experimentally by comparing Figs. 11–14 with Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The asymmetrical CHBMLI produces more number of output voltage levels with the same circuit configuration, that of symmetrical. However, it has different component ratings, and it is challenging to achieve the power balance [18]. Some modified MLIs are reported in [19][20][21] for PV applications, but the larger component count and the control complexity are the drawbacks of those MLIs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, by considering an asymmetrical configuration, where the DC sources amplitudes are properly chosen, it is possible to increase the voltage levels by maintaining the same topology structure. As suggested in [11] and [12], the authors have demonstrated that by maintaining a 5-level CHB topology structure it is possible to obtain a 7-level and 9-level voltage waveform. In this way, the converter performance can be improved without increasing the hardware complexity.…”
Section: Introductionmentioning
confidence: 98%